Bilocal periodic problem for the Sturm-Liouville and Dirak operators as well as certain applications in the theory of nonlinear dynamic systems. I - Bogolyubov (juniour), N. N.; Prikarpatsky , A. K. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
Isospectral problems for operator-valued Sturm-Liouville and Dirac differential expressions are considered. Within the framework of the gradient method, one establishes the complete integrability of the Lax associated nonlinear Hamiltonian systems with a bilocal implectic pair of Noetherian operators on a manifold of integral operators.